Risk of HIV infection among adolescent girls and young women in age-disparate relationships in sub-Saharan Africa - Bajunirwe, Francis; Semakula, Daniel; Izudi, Jonathan (Aids, 2020)
Objective: To determine the association between age-disparate relationships and risk of HIV infection among adolescent girls and young women (AGYW) aged 15–24 years. Design: Systematic review and meta-analysis of published studies until January 5, 2020 in sub Saharan Africa (SSA). Methods: We searched several electronic databases, grey literature, and hand searched reference list of included studies to identify eligible studies for data abstraction. We assessed the quality of included studies using Newcastle–Ottawa Scale for nonrandomized studies. The DerSimonian–Laird random effects model was used to pool the overall results using risk ratios (RR), presented in a forest plot with 95% confidence interval (CI) and predictive interval. Heterogeneity was assessed with Cochrane’s Q-test and quantified with I2 values. Publication bias was checked with funnel plots and Egger’s test. Results: We included 24 studies with an overall sample size of 33 390. Data show that age-disparate relationships were significantly associated with unprotected sexual intercourse (pooled RR, 1.57; 95% CI, 1.34–1.83; 95% predictive interval, 1.22– 2.02), and higher risk for HIV infection (pooled RR, 1.39; 95 CI, 1.21–1.60; 95% predictive interval, 0.80–2.42). Studies included in pooling risk of unprotected sexual intercourse were largely homogeneous (I2-value¼ 0.0, P¼0.79) whereas those for HIV infection were heterogeneous (I2- value ¼ 89.0%, P<0.01). We found no publication bias and no study influenced the meta-analytic results. Conclusion: Age-disparate relationships among AGYW are associated with increased risk of unprotected sexual intercourse and HIV infection in SSA. HIV prevention interventions should target this sub-population.
Keywords: Age-disparate relationship; HIV infection; Sub-Saharan Africa; Unprotected sex